Differences in overweight/obesity prevalence by demographic characteristics and self-weight misperception status. (February 2021) - Alami, Ali; Jafari, Alireza; Hosseini, Zahra
Summary: Background & aims: Increasing the prevalence of overweight and obesity is one of the main concerns of health systems of the world. This research was conducted to estimate the prevalence of overweight/obesity and its related factors in the Eastern part of Iran. Methods: An analytical, cross-sectional study was conducted among 1048 inhabitants aged between 15 and 64 years who lived in Gonabad and Bajestan, two districts locating in the East of Iran, in 2016. A probability proportional to size stratified sampling was used to select the participants. We applied a checklist to collect the required data. Analyzing the data, we used t-test, χ2, and ANOVA. A significant level of 0.05 was considered in this study. Results: Total prevalence of overweight/obesity was 43.8%. There were significant associations between overweight/obesity and age (P < 0.001), sex (P = 0.008 in Gonabad, P = 0.004 in Bajestan), marital status (P < 0.001, in Gonabad, P = 0.001 in Bajestan), and job (P < 0.001). There was also a discrepancy between the participants' self-perception of weight and their real weight status. Conclusion: The findings of the present study showed a high prevalence of overweight/obesity among women, government employees, and married individuals. Therefore, focusing on these groups in implementing weight control interventions is recommended. According to the high prevalence of obesity in housewives as well as the role of women to control the normal weight of their family members via providing healthy food, it seems that one of the most effective groups in the programs would be housewives. Besides, strengthening health literacy is recommended to eliminate self-weight misperception.